ERECTA signaling controls Arabidopsis inflorescence architecture through chromatin‐mediated activation of PRE1 expression. Issue 4 (13th March 2017) - Cai, Hanyang; Zhao, Lihua; Wang, Lulu; Zhang, Man; Su, Zhenxia; Cheng, Yan; Zhao, Heming; Qin, Yuan
Summary: Flowering plants display a remarkable diversity in inflorescence architecture, and pedicel length is one of the key contributors to this diversity. In Arabidopsis thaliana, the receptor‐like kinase ERECTA (ER) mediated signaling pathway plays important roles in regulating inflorescence architecture by promoting cell proliferation. However, the regulating mechanism remains elusive in the pedicel. Genetic interactions between ERECTA signaling and the chromatin remodeling complex SWR1 in the control of inflorescence architecture were studied. Comparative transcriptome analysis was applied to identify downstream components. Chromatin immunoprecipitation and nucleosome occupancy was further investigated. The results indicated that the chromatin remodeler SWR1 coordinates with ERECTA signaling in regulating inflorescence architecture by activating the expression of PRE1 family genes and promoting pedicel elongation. It was found that SWR1 is required for the incorporation of the H2A.Z histone variant into nucleosomes of the whole PRE1 gene family and the ERECTA controlled expression of PRE1 gene family through regulating nucleosome dynamics. We propose that utilization of a chromatin remodeling complex to regulate gene expression is a common theme in developmental control across kingdoms. These findings shed light on the mechanisms through which chromatin remodelers orchestrate complex transcriptional regulation of gene expression in coordination with a developmental cue.